Aesthetic All-ceramic Restorations. CAD-CAM System - FERNANDEZ BODEREAU, E.; Bessone, LM; Gabriela Inés Cabanillas (2019)
ABSTRACT: Aesthetic dentistry is dedicated to imitate nature by maintaining the size, shape, color and symmetry. Technology has developed metal-free ceramic materials so capable of reproducing a natural appearance, that traditional materials have been replaced by them. The yttrium partially-stabilized zirconium oxide does not only have the advantage of being extremely resistant, but it is also highly translucent. It has a translucency that allows about 50% of the incident light to pass through, a characteristic that is vital for providing a more natural appearance to restorations. The duration of scanning and milling procedures will depend on the size of the object, the number of objects processed and the steps selected (CAM or CAD/CAM). The framework of the densely sintered zirconium oxide with its precise fit is veneered with the veneering ceramic developed especially for this purpose. Almost in all cases, there are several treatment alternatives for the same diagnosis. The success of these restorations will be predicted as long as it is founded on sustaining biological principles. The aim of this paper is to concisely present the sequences for a clinical treatment in a schematic and illustrative manner.